2022
DOI: 10.1101/2022.02.13.480248
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microbial dysbiosis and metabolic disorders promote rheumatoid arthritis across successive stages: a multi-omics cohort study

Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory disease that typically progresses through four stages, from mild stiffness to severe disability. The gut-joint axis is critical in RA pathogenesis, while its dynamic patterns and regulatory mechanisms throughout RA progression remain unknown. Here, we performed fecal metagenomic and serum metabolomic studies on a cohort of 122 patients from four distinct RA stages. Microbial dysbiosis and metabolomic disorders present stage-specific patterns and played crucia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
(175 reference statements)
1
0
0
Order By: Relevance
“…In this study, we also observed a reduced presence of the lipopolysaccharide metabolism module in certain subgroups of patients with long-standing RA. Our findings are consistent with previous research [41,42] showing that the microbiota of these patients have an increased ability to degrade ascorbate, which may contribute to disease development. According to the study by Pattison et al, it was reported that ascorbate prevents the development of inflammatory arthritis [43].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we also observed a reduced presence of the lipopolysaccharide metabolism module in certain subgroups of patients with long-standing RA. Our findings are consistent with previous research [41,42] showing that the microbiota of these patients have an increased ability to degrade ascorbate, which may contribute to disease development. According to the study by Pattison et al, it was reported that ascorbate prevents the development of inflammatory arthritis [43].…”
Section: Discussionsupporting
confidence: 93%